KETERLIBATAN MASYARAKAT DALAM PENGEMBANGAN AKSESIBILITAS DI OBJEK WISATA AIR TERJUN LUBUAK BATANG KABUPATEN 50 KOTA PROVINSI SUMATERA BARAT - Haula Ishro; Firdaus Yusrizal (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Attraction Waterfall Lubuak Batang one of the attractions waterfalls in District 50 City which has a height of approximately 50-70 meters. The uniqueness of this waterfall is flanked by two high stone walls and in the middle of the stone wall the waterfall is flowing beautifully, even during the dry season this waterfall is no drought and access to this tourist attraction is difficult to achieve and not far Of the Community involved.This study aims to determine the development of accessibility in waterfall Lubuak Batang and to find out how the response of visitors to accessibility to this attraction. This research uses qualitative method with survey approach, that is find out visitor response about accessibility at Lubuak Batang waterfall tourism area. Where the researchers tried to explain how the community in the development of accessibility As a questionnaire distributed as many as 50 people. While the data completion technique in this research use interview, observation, questionnaire, and documentation.Keywords : Involvement, community, accessibility, Lubuak Batang